Implementation of Scrum Method in the Learning Activity Monitoring Feature Outside the Study Program - -, Atik Nurmasani; Ilham, Muhammad Rohmadi; Anggit Dwi Hartanto (Jurnal Komputer Terapan, 2024)
Learning activities outside the study program can be participated by active students in the current semester through the credit recognition mechanism according to the study program policy. These activities are monitored by Field Supervisors (DPL) through certain communication media. The obstacles that arise such as students not contacting DPL or communicating with DPL, not reporting activities regularly, only asking for a signature on the final report, and only asking DPL to fill out an activity assessment. The activity recording information system that available only has features for submitting proposals, recording activities and reporting activities for study program admin users. So that it is necessary to develop a feature for monitoring learning activities outside the study program to make it easier for DPL to monitor student activities in certain semesters. The information system was created using the MySQL database and the Codeigniter 3 framework. Feature development was created using the Scrum method with a focus on determining priority features, working on priority features and reviewing the results of feature work. This can help to get information system output quickly according to development needs